A low complexity pre‐distortion scheme for power amplifier linearization in wideband applications. (17th August 2016) - Varahram, Pooria; Dooley, John; Finnerty, Keith; Farrell, Ronan
Summary: In this paper, a nonlinear autoregressive with exogenous inputs (NARX) digital pre‐distortion scheme to linearize power amplifiers is proposed. The proposed NARX digital pre‐distortion gives better accuracy and spectral leakage suppression compared with other commonly used Volterra‐based techniques. The stability criterion of the NARX digital pre‐distortion is derived from the frequency domain analysis. Simulation is carried out with a 20 MHz single carrier long‐term evolution signal and two‐carrier long‐term evolution signal and instantaneous to average ratio of 6.2 dB at 0.01% complementary cumulative distribution function (CCDF). The results of simulation analysis show a slight improvement in adjacent channel leakage ratio performance with 30% reduction in the number of floating point operations compared with conventional pre‐distortion techniques. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A pre‐distortion scheme based on nonlinear autoregressive with exogenous inputs to linearize power amplifiers is proposed. The stability criterion is derived and proved analytically. Simulations with a single carrier long‐term evolution signal with 20‐MHz bandwidth show 30 % reduction in the number of floating point operations with similar adjacent channel leakage ratio performance compared with conventional pre‐distortion techniques.